2022
DOI: 10.3389/fpsyg.2022.970444
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of corporate social responsibility and sustainable supply chain management in shaping the consumers’ intention to use sharing platforms

Abstract: Sustainable supply chain management (SSCM) in sharing economy platforms supports resource management and achieves environmental sustainability. Corporate social responsibility (CSR) is an essential pillar of sustainability, but the link between CSR and SSCM has been missing in the literature. Therefore, the current study intends to examine the connection between CSR and SSCM practices in sharing economy-based platforms. This study has applied the means-end theory to understand customer intention in the sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…In an attempt to understand the underlying factors that may lead to the consumption of environmental-friendly products, researchers highlight that the psychographic traits of consumers might be responsible for an impact on their pro-environmental buying behavior (Sahelices-Pinto et al, 2021;Li et al, 2022). Therefore, an extended model of TPB with the integration of motivational factors taken from SDT has been utilized to conduct a comprehensive study in the context of the emerging economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to understand the underlying factors that may lead to the consumption of environmental-friendly products, researchers highlight that the psychographic traits of consumers might be responsible for an impact on their pro-environmental buying behavior (Sahelices-Pinto et al, 2021;Li et al, 2022). Therefore, an extended model of TPB with the integration of motivational factors taken from SDT has been utilized to conduct a comprehensive study in the context of the emerging economy.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to understand the underlying factors that may lead to the consumption of environmental-friendly products, researchers highlight that the psychographic traits of consumers might be responsible for an impact on their pro-environmental buying behavior (Sahelices-Pinto et al. , 2021; Li et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies demonstrate that companies possessing GDC are more aptly equipped to fulfill the consumers' desire for sustainable products and adhere to stringent environmental regulations (Demirel and Kesidou, 2019). Businesses can foster their competitive edge by adopting GDC and projecting a favorable image of environmental responsibility, thereby attracting eco-conscious consumers (Sarwar et al, 2023;Li et al, 2022).…”
Section: Green Dynamic Capabilities Supply Chain Agility and Green Co...mentioning
confidence: 99%
“…Past studies have found that exposure to information about environmental issues and the impacts of human actions can lead to increased ENB and behaviors (Shah et al, 2021;Han and Xu, 2020;Huang, 2016). IP is a crucial factor that contributes to individual awareness of environmental issues (Li et al, 2023). Researchers found that IP have significant influence pro-environmental behavior and PN of individual regarding e-waste recycling (Wang et al, 2022) and waste sorting intention (Li et al, 2023).…”
Section: Information Publicity On Pro-environmental Beliefsmentioning
confidence: 99%
“…However, researchers did not pay much attention on the relationship between IP, ENB and PN, which in turn lead to visiting green hotels. A recent study conducted by Li et al (2023) revealed the significant impact of IP on individual proenvironmental behavior. The authors emphasize the importance of examining the influence of IP in specific areas that shape individual pro-environmental behavior.…”
Section: Introductionmentioning
confidence: 99%